Studi Analisis Epistemologi dalam Filsafat Pendidikan Islam di SMK Muhammadiyah 03 Nogosari Boyolali - Setyawati, Hidayati Rina (Lembaga Yasin AlSys, 2026)
Although the philosophy of Islamic education has received considerable scholarly attention, studies that specifically examine the application of Islamic epistemology in the context of Islamic vocational education remain limited. This study aimed to analyze the application of epistemology within the philosophy of Islamic education at SMK Muhammadiyah 03 Nogosari Boyolali. A qualitative approach with a case study design was employed, involving three teachers selected through purposive sampling. Data were collected through semi-structured interviews and document analysis, and subsequently examined using thematic analysis. The findings indicate that the learning process at SMK Muhammadiyah 03 Nogosari Boyolali integrates sources of knowledge derived from revelation, reason, and empirical experience; Islamic Religious Education instruction positions revelation as the primary foundation, whereas general and vocational subjects optimize the role of reason and experience framed by Islamic values. These findings contribute to the development of epistemological theory in Islamic education and broaden understanding of knowledge integration in the context of Islamic vocational education. The study concludes that Islamic epistemology plays a central role in shaping holistic education and recommends that Islamic educational institutions consistently integrate epistemological values throughout the curriculum. The implications of this research include theoretical contributions to enriching the literature on the philosophy of Islamic education and practical implications for the development of policies and instructional practices in Islamic vocational schools, while also opening opportunities for further inquiry into ontological and axiological aspects of Islamic education.